Formation of a Monetary Union among Asean+3 - Md. Yusof, Aimy (2004)
Following the successful establishment of the European Union (EU) in 1993, questions have been raised to whether we should have a monetary union in East Asia. Are we ready to form such regional integration? In Europe, they have previously used a set of convergence criteria, known as the Maastricht Convergence Criteria, as a benchmark to measure a candidate country’s competency prior to joining the EU. The criteria set involves inflation rate, interest rate, exchange rate, deficit/GDP ratio and debt/GDP ratio.